Analysis of the Balanced Scorecard as a Tool in Setting Business Strategies at the Uli Motor Workshop - Surayya, Laila (Yayasan Mitra Peduli Indonesia, 2023)
This research aims to compile a strategy based on the balanced scorecard at the Uli Motor Workshop. First, this research explains how the company's general strategy is determined through SWOT, which is then divided into four perspectives: the financial perspective, the customer perspective, the internal business process perspective and the learning growth perspective. Compiling this balanced scorecard begins by translating the company's vision, mission, long-term goals and strategic plans. Then, the strategic purpose of each perspective is formulated. Finally, it is continued with the cause-and-effect relationship between the perspectives and forms a map of the company's strategy as a whole.